Benzoxazole/benzothiazole‐derived VEGFR‐2 inhibitors: Design, synthesis, molecular docking, and anticancer evaluations. Issue 12 (9th October 2019) - El‐Helby, Abdel‐Ghany A.; Sakr, Helmy; Eissa, Ibrahim H.; Al‐Karmalawy, Ahmed A.; El‐Adl, Khaled
Abstract: A novel series of benzoxazole/benzothiazole derivatives 4a–c –11a–e were designed, synthesized, and evaluated for anticancer activity against HepG2, HCT‐116, and MCF‐7 cells. HCT‐116 was the most sensitive cell line to the influence of the new derivatives. In particular, compound 4c was found to be the most potent derivative against HepG2, HCT‐116, and MCF‐7 cells, with IC50 values = 9.45 ± 0.8, 5.76 ± 0.4, and 7.36 ± 0.5 µM, respectively. Compounds 4b, 9f, and 9c showed the highest anticancer activities against HepG2 cells with IC50 values of 9.97 ± 0.8, 9.99 ± 0.8, and 11.02 ± 1.0 µM, respectively, HCT‐116 cells with IC50 values of 6.99 ± 0.5, 7.44 ± 0.4, and 8.15 ± 0.8 µM, respectively, and MCF‐7 cells with IC50 values of 7.89 ± 0.7, 8.24 ± 0.7, and 9.32 ± 0.7 µM, respectively, in comparison with sorafenib as reference drug with IC50 values of 9.18 ± 0.6, 5.47 ± 0.3, and 7.26 ± 0.3 µM, respectively. The most active compounds 4a–c, 9b, c, e, f, h, and 11c, e were further evaluated for their VEGFR‐2 inhibition. Compounds 4c and 4b potently inhibited VEGFR‐2 at IC50 values of 0.12 ± 0.01 and 0.13 ± 0.02 µM, respectively, which are nearly equipotent to the sorafenib IC50 value (0.10 ± 0.02 µM). Furthermore, molecular docking studies were performed for all synthesized compounds to assess their binding pattern and affinity toward the VEGFR‐2 active site. Abstract : A novel series of benzoxazole/benzothiazole derivatives 4a–c –11a–e were designed, synthesized, and evaluated for anticancer activity against HepG2, HCT‐116, and MCF‐7 cells. HCT‐116 was the most sensitive cell line to the influence of the new derivatives. The most active compounds were further evaluated for their VEGFR‐2 inhibition. Compounds 4c and 4b potently inhibited VEGFR‐2 at IC50 values nearly equipotent to that of sorafenib.